(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Amphibians were the first group of vertebrates that were adapted in the course of evolution to both the aquatic and terrestrial way of life. In the evolutionary history of vertebrates, amphibians have a special position for first living on the ground . Among fully aquatic fishes and actual land amniotes, amphibians are intermediate. Amphibian species were perpetuated successfully and their survival had to do with the growth of extremities, lungs, other anatomical modifications and, particularly, the evolution of new reproductive strategies in the new terrestrial world . Since amphibians are poikilothermic and also because most of them rely on water for their reproduction, the constantly changing climatic factors such as air and water greatly affect their reproductive activities. Temperature (Delgado et al., 1992 Sumida et al., 2007). Rainfall, daylength and relative humidity.